Assessment of wind energy resources in Chad, Central Africa, using 100-m wind data from ERA5 reanalysis - Ali Ahmat Younous; Serigne Abdoul Aziz Niang; Astou Sarr; Mamadou Simina Drame (Energy Exploration & Exploitation)
This study provides a climatological assessment of wind resources in Chad using 100-m wind data from the ERA5 reanalysis. The results highlight spatio-temporal variations in wind potential, Enabling the identification of climate zones suitable for wind farm development. Wind speeds range from 1.5 to 11 m/s, with increasing gradients from south to north. Maximum wind speeds are observed between autumn and spring, particularly from October to April, while minimum speeds, below 5 m/s, occur during the wet season. A distinct diurnal cycle is noted, with nighttime wind speeds averaging 26% higher than daytime speeds. Winds predominantly blow in favorable directions, primarily toward the northeast. The study indicates that almost the entire northern region of Chad (north of 15°N latitude) is particularly favorable for wind farm installations, except for areas around the Tibesti mountain range, where wind speeds remain low due to the presence of a permanent anticyclone. Three zones are identified as particularly promising: the region around Faya, the far northeastern part of the country, and the area around Amjarass. Additionally, long-term analysis reveals a slight decrease in 100-m wind speeds, possibly linked to the increased frequency of La Niña events over the past decade. In conclusion, this study provides a comprehensive assessment of Chad's wind potential, emphasizing that the most suitable areas are located between the Saharan and Sahelian zones.